Проблема містобудівного розвитку системи санітарного очищення великого міста - Золотар, Людмила Вячеславівна; Zolotar Liudmyla (КНУБА, 2020)
Проблемою антропогенного впливу на навколишнє середовище та якістю санітарного очищення міста цікавляться в господарських, екологічних, санітарно-епідеміологічних та економічних напрямках, але багато методологічних питань залишаються не розглянутими з містобудівної сторони. Науково-обґрунтоване рішення розміщення первинних пунктів збору побутових відходів на житлових територіях міста та методологія системного підходу до організації санітарного очищення міста являється початковими питаннями в вирішенні проблеми поводження з побутовими відходами. The economic, ecological, sanitary, and epidemiologic direction of problem of anthropogenous impact on environment and quality of waste management of the city are interested. The methodological questions of urban development of waste management are researched is not much well. The scientific substantiation of methodological system of waste management and distribution of waste collection points are the first solution of the problem in waste management. The organization of the system of sanitary cleaning of residential areas is based on the principles of a systematic approach: the principle of integrity means that the system of sanitary purification has clearly expressed spatial-planning and technological-organizational boundaries; the principle of hierarchical structure involves consideration of urban and technological organization of the system of sanitary purification in the fullness of its elements, essential connections between them. The basis of the method is the satisfying of urban planning principles, requirements and conditions of the territory when choosing a method of collecting sanitary cleaning. The decision on technological or organizational-technological way of collecting household waste is made at the third or second technological level and is based on urban planning requirements, analysis of the territory, and is made according to a number of restrictions that characterize the territory. The main urban planning restrictions when choosing a method of collection: territorial restriction, population density of the block, the perimeter of the territory of the block, the area of the territory within the streets, the area of influence of the waste transfer station.
Проблема градостроительного развития системы санитарной очистки большого города.
The problem of urban development of waste management in the big city.
Keywords: санітарне очищення міста; первинні пункти збору; побутові відходи; житлові території міста; містобудування; waste management; waste collection points; household waste; residential areas of the city; urban planning